2018
DOI: 10.21608/jpp.2018.36600
|View full text |Cite
|
Sign up to set email alerts
|

Potato Growth and Yield Attributes as Affected by Boron and Selenium Foliar Application

Abstract: Enhancing potato growth and yield attributes via both Boron (Br) and Selenium (Se) is a great potential nowadays. Therefore, the present investigation was done to study the effe ct of Boron and Selenium singly or in combination as foliar application on plant growth, yield and quality of two potato cultivars 'Lady Rosetta and Caruso' during both seasons of 2016/2017 and 2017/2018. The experimental layout was split plots system in a randomized complete blocks design with three replications. Cultivars were arrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
1
6
1
Order By: Relevance
“…As boron was effectively absorbed by leaves, and hence increased fresh biomass of potato crop [ 31 ]. These findings in contrast to recent work of [ 32 ], who urged that no significant differences were observed between soil and foliar applied boron on biological yield of potato tuber.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As boron was effectively absorbed by leaves, and hence increased fresh biomass of potato crop [ 31 ]. These findings in contrast to recent work of [ 32 ], who urged that no significant differences were observed between soil and foliar applied boron on biological yield of potato tuber.…”
Section: Discussioncontrasting
confidence: 99%
“…The recent work of Shnain et al [ 40 ] supported our findings, who observed that maximum shelf life of tomato fruit was due to foliar application of boron at the rate of 1.25 g L -1 . The present results also suggest that boron applied through any method reduced the loss of water from potato tubers, because boron helps to maintain membrane stability [ 32 ] and perhaps boron also created firmness in the potato tubers [ 4 , 6 ].…”
Section: Discussionmentioning
confidence: 91%
“…Potato ( Solanum tuberosum L) is a herbaceous plant belonging to the Solanaceae family that grows up to 100 cm (40 inches) in length ( Alkharpotly, Roshdy & Mady, 2018 ; Shirur, Channakeshava & Bhairappanavar, 2021 ). Potatoes produce tubers with a thickened stem and found in the Punjab province in Pakistan, especially in the area of: Okara, Sahiwal, Gujranwala, and Sheikhupura ( Shirur, Channakeshava & Bhairappanavar, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the potato will become a leading crop and could be used to meet nutritional needs globally ( Zheng et al, 2018 ). However, many areas of potato production in developing nations are located in semi-arid regions, where drought stress negatively affects the harvest, threatening the sustainability of the potato industry ( Alkharpotly, Roshdy & Mady, 2018 ). Hence, there is a need to enhance potato cultivation in areas with periodic drought stress due to decreasing water resources.…”
Section: Introductionmentioning
confidence: 99%
“…Foliar spray of potato plants with B at different rates was studied by El-Banna and Abd El-Salam (2005), El-Dissoky and Abdel-Kadar (2013) and Alkharpotly et al (2018). Their studies appeared the superiority effect of spraying boron at 75, 60 and 100 ppm in the three studies respectively.…”
Section: Introductionmentioning
confidence: 99%